2008
DOI: 10.1037/a0013306
|View full text |Cite
|
Sign up to set email alerts
|

Therapist immediacy in brief psychotherapy: Case study II.

Abstract: Immediacy was examined in a 17-session case of brief therapy with a bright, articulate, inner-city, African American female client seeing an interpersonally oriented, White, male therapist. The main types of therapist immediacy were reinforcing the client for in-session behavior, inviting the client to collaborate, inquiring about client reactions to therapy, and reminding the client that it was okay to disagree with him. An in-depth qualitative examination of the seven most extensive/salient immediacy events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(114 citation statements)
references
References 39 publications
6
107
1
Order By: Relevance
“…In addition to this research, Hill and colleagues presented two single case studies of brief interpersonal therapy that focus on the therapeutic relationship and examine the qualitative nature of theses interventions as well as their impact on client involvement and outcome (Hill et al, ; Kasper, Hill, & Kivlighan, ). The studies showed that a focus on the therapeutic relationship can take on various forms (confronting and challenging, supportive and empowering etc.…”
mentioning
confidence: 99%
“…In addition to this research, Hill and colleagues presented two single case studies of brief interpersonal therapy that focus on the therapeutic relationship and examine the qualitative nature of theses interventions as well as their impact on client involvement and outcome (Hill et al, ; Kasper, Hill, & Kivlighan, ). The studies showed that a focus on the therapeutic relationship can take on various forms (confronting and challenging, supportive and empowering etc.…”
mentioning
confidence: 99%
“…Case analyses by Hill et al (2008); Kasper, Hill, &Kivlighan (2008), andMayotte-Blum et al (2012) have showed that skilful use of immediacy on the part of the therapist was perceived by clients as showing caring and helpfulness, tended to facilitate expression of painful emotional material, and contributed to the client being able to develop closeness with other people in their life.…”
Section: Persistencementioning
confidence: 99%
“…It is therefore possible to develop a more comprehensive appreciation of the case of Krista (Hill et al, ) by contrasting it with other cases in this body of work. Particularly relevant are two recent cases from this research group that have explored the role of immediacy in therapy (Hill et al ; Kasper, Hill, & Kivlighan, ). Unlike these earlier cases, which were characterised by quite high levels of therapist use of immediacy, Krista's therapist appeared to make minimal use of immediacy, despite high levels of competence in other skills.…”
Section: Case Study Research In Counselling and Psychotherapy: Exemplmentioning
confidence: 99%